Three-dimensional visualisation of the feto-placental vasculature in humans and rodents. (October 2021) - James, J.L.; Tongpob, Y.; Srinivasan, V.; Crew, R.C.; Bappoo, N.; Doyle, B.; Gerneke, D.; Clark, A.R.; Wyrwoll, C.S.
Abstract: Adequate development of the feto-placental circulation is critical for placental exchange function and healthy fetal growth. Understanding the structure of this circulation and how it informs fetal outcomes is important both in the human placenta, and the rodent, a purported comparative experimental model. Vascular casting and micro-CT imaging approaches enable detailed quantification of the complex vascular relationships in the feto-circulation, and provide detailed data to parameterise in silico models. Here, to assist researchers to apply these technically challenging methods we provide detailed approaches to cast and image; 1) human placentas at the cotyledon-level, and 2) whole rodent placentas. Highlights: 3D vascular casts of human and rodent placental cotyledons were generated. Technical recommendations are supplied to help with successful implementation. Quantification of 3D vessel relationships will aid multiscale in silico modelling.